The Topical Theme Depicted in the Talks of Education in Indonesian’s TEDx : a Systemic Functional Linguistics Approach - Danang Satria Nugraha (Universitas Lancang Kuning, 2023)
The education-related TEDx presentations delivered by Indonesian speakers are a distinct linguistic phenomenon. It is a language in use where the message is communicated entirely through spoken speech as opposed to speaking itself. In light of systemic functional linguistics (SFL), this study examines the management of topical theme in relation to the message organisation of TE in TEDx. The aim of this study was to pinpoint and define the message's current theme in the TEDx format. Using the documentation method, the information was gleaned from an official TEDx broadcaster online. Two methods of analysis have been used: detailed text fragmentation and transcription. Following the analysis, the findings were presented and their theoretical SFL-based interpretation was given. This study shows that the phrasal and clausal forms of language, which are the constructional units of language, have taken on the topical theme in TE of TEDx. Phrasal constructs can be categorised into four different categories: noun phrase (NP), verb phrase (VP), adjective phrase (AP), and prepositional phrase (PP). The topical theme has also been functionalized as a component of other themes and the chain for coherence. This study recommended more examination of the organisation of the other component of the message. To ensure that the entire description of the thematic structure of TE in TEDx is respected, the combinatory analysis of theme and rheme will be essential.